2022
DOI: 10.1186/s12879-022-07647-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibody waning after immunosuppressive chemotherapy and immunomodulators, re-immunization considerations in pediatric patients with malignancy and chronic immune thrombocytopenic purpura

Abstract: Introduction Immunosuppressive chemotherapy increase the risk of vaccine-preventable infectious diseases in children; nevertheless, chemotherapy may result in delay or miss updated immunization schedules. The predictable antibody waning after incomplete primary immunization series may be intensified at the end of chemotherapy. This study aimed to investigate post-chemotherapy vaccine immunity waning at the end of immunosuppressive therapy in children with malignancy and hematologic disorders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Through in-depth investigation of its mechanism of action, we found that the vaccine can effectively regulate the tumor microenvironment and enhance the anti-tumor immune response of the body. Studies [251][252][253] have shown that mannose-modified nanoparticles can promote uptake and endocytosis of tumor cells through specific targeting, thereby improving the efficiency of antigen delivery and activating the activity of tumor-associated antigen-specific T cells. In addition, the vaccine can also induce immune cells in the tumor microenvironment, such as plasma cells and dendritic cells, to release proinflammatory factors, and inhibit the function of immunosuppressive cells, thereby promoting the activation and expansion of T cells, enhancing the killing ability of cytotoxic T lymphocytes, and finally realizing the effective elimination of tumors.…”
Section: Enlightenment and Research Prospect Of Preclinical Researchmentioning
confidence: 99%
“…Through in-depth investigation of its mechanism of action, we found that the vaccine can effectively regulate the tumor microenvironment and enhance the anti-tumor immune response of the body. Studies [251][252][253] have shown that mannose-modified nanoparticles can promote uptake and endocytosis of tumor cells through specific targeting, thereby improving the efficiency of antigen delivery and activating the activity of tumor-associated antigen-specific T cells. In addition, the vaccine can also induce immune cells in the tumor microenvironment, such as plasma cells and dendritic cells, to release proinflammatory factors, and inhibit the function of immunosuppressive cells, thereby promoting the activation and expansion of T cells, enhancing the killing ability of cytotoxic T lymphocytes, and finally realizing the effective elimination of tumors.…”
Section: Enlightenment and Research Prospect Of Preclinical Researchmentioning
confidence: 99%
“…[12][13][14] Protective antibodies may drop regardless of a patient's vaccination status before chemotherapy or donor or recipient vaccination status before transplantation. 13,[15][16][17][18][19] Fortunately, revaccination or resumption of indicated vaccinations following completion of cancer therapy can produce protective immunity in these children, even in patients with some ongoing immunosuppression. [19][20][21]…”
Section: S2 Of S12mentioning
confidence: 99%